عقود الإذعان وأحكامها الفقهية - مومن بكوش, البشير; عاد, عبد اللطيف; عباس, محمد الصالح (University of Eloued-جامعة الوادي, 2022)
يدرس هذا البحث موضوع عقود الإذعان، عن طريق تتبع مسائلها؛ من حكم وأركان وشروط وأنواع وخصائص، محاولين الكشف عن أهم الأحكام الشرعية التي تتعلق بهذا العقد المستحدث، والتي لم يتطرق لها الفقهاء القدامى ولم تكن معروفة عندهم، فجاء هذا البحث من أجل ضبط أحكام ومسائل هذا العقد من خلال ما سطره الفقهاء من أحكام وقواعد قعدوها تضبط المعاملات المالية بضوابط الشرع الحنيف. فكان هذا البحث بيان لأهمية العلم بهذه الأحكام الشرعية وتفعيلها في الواقع العملي، لما فيها من تحقيق منافع عظيمة للفرد المسلم والمجتمع، في كل الميادين، وبيان ما في الجهل بها من مخاطر، أو التهاون في تجسيدها عمليا من مفاسد تضر بالأفراد والمجتمع بأسره.This research studies the subject of compliance contracts، by tracing its issues ; From rule and pillars And conditions، types and characteristics، trying to reveal the most important legal provisions related to this contract The new، which the ancient jurists did not address and was not known to them، so this research came from In order to set the provisions and issues of this contract through what the jurists wrote of the provisions and rules that they set Financial transactions are governed by the principles of Shariah law. This research was a statement of the importance of knowing these legal rulings and activating them in practice It contains great benefits for the Muslim individual and society، in all fields، al shows the ignorance of it Risks، or negligence in their practical embodiment of evils that harm individuals and society as a whole.
مذكرة ماستر
Keywords: العقود - التكييف الفقهي - الاحتكار; Contracts-juristic adaptation-monopoly